PENDAMPINGAN PROGRAM PEMBIASAAN ENGLISH VOCABULARY DI PESANTREN TRADISIONAL DARUL HIKMAH PRASUNG - Sulistyaningsih; Vebriary Eka; Fitriyah Fitriyah; Amaliah Amaliah (STKIP PGRI Sidoarjo, 2019)
Universities are not only the place to produce human resources that have high intellect, but also should provide value to the surrounding community. Specifically, the authors team chose to do society dedication in the area which closest to the campus, that is Traditional Islamic Boarding School Darul Hikmah. The problem is that the level of need for the cottage will be very high. On one side, the board of the lodge wants to answer the challenges of the era of the importance of their students to master English to be equal to other students by means of the English Vocabulary Habit Program. The purpose is to give dedication in the form of Assistance for the English Vocabulary Habit Program at Prasung Islamic Boarding School. There are 30 students and the sample used by the team is 10. The method of implementing this program is by educating students who lackknowledge of English. The results of societydedication have had a significant impact, some errors such as writing vocabulary on the list of vocabularies can be improved. Students are also very enthusiastic about learning vocabulary taught by direct method. The original teacher in the Islamic boarding school (ustadh and ustadhah) can adopt more contextual, meaningful and communicative vocabulary learning.